2018
DOI: 10.1002/anie.201802576
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dinitrogen Reduction to Ammonia at a Triamidoamine–Titanium Complex

Abstract: Catalytic reduction of N2 to NH3 by a Ti complex has been achieved, thus now adding an early d‐block metal to the small group of mid‐ and late‐d‐block metals (Mo, Fe, Ru, Os, Co) that catalytically produce NH3 by N2 reduction and protonolysis under homogeneous, abiological conditions. Reduction of [TiIV(TrenTMS)X] (X=Cl, 1A; I, 1B; TrenTMS=N(CH2CH2NSiMe3)3) with KC8 affords [TiIII(TrenTMS)] (2). Addition of N2 affords [{(TrenTMS)TiIII}2(μ‐η1:η1‐N2)] (3); further reduction with KC8 gives [{(TrenTMS)TiIV}2(μ‐η1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 75 publications
12
116
0
Order By: Relevance
“…Previously, we reported that [Ti(Tren TMS )Cl] [ 1 ; Tren TMS ={N(CH 2 CH 2 NSiMe 3 ) 3 } 3− ] can be reduced by K (K mirror, KC 8 , or KC 10 H 8 ) to give [Ti(Tren TMS )]; this species can bind to N 2 to give the end‐on:end‐on N 2 complex [{Ti(Tren TMS )} 2 (N 2 )], and further reduction with K gives [{Ti(Tren TMS )} 2 (N 2 K 2 )] ( 2 ), which formally contains N 2 4− where the N−N bond is retained (Scheme ). Nevertheless, 2 produces up to 18 equivalents of NH 3 when treated with excess H + /e − . As it was clear that K ( E °=−2.92 V) plays a cooperative, directing role in that reduction chemistry, we investigated what effect replacing it with the milder reducing agent Mg ( E °=−2.37 V) would have .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that [Ti(Tren TMS )Cl] [ 1 ; Tren TMS ={N(CH 2 CH 2 NSiMe 3 ) 3 } 3− ] can be reduced by K (K mirror, KC 8 , or KC 10 H 8 ) to give [Ti(Tren TMS )]; this species can bind to N 2 to give the end‐on:end‐on N 2 complex [{Ti(Tren TMS )} 2 (N 2 )], and further reduction with K gives [{Ti(Tren TMS )} 2 (N 2 K 2 )] ( 2 ), which formally contains N 2 4− where the N−N bond is retained (Scheme ). Nevertheless, 2 produces up to 18 equivalents of NH 3 when treated with excess H + /e − . As it was clear that K ( E °=−2.92 V) plays a cooperative, directing role in that reduction chemistry, we investigated what effect replacing it with the milder reducing agent Mg ( E °=−2.37 V) would have .…”
Section: Methodsmentioning
confidence: 99%
“… The Ti complex 1 gives different N 2 reduction products depending on the nature of the reducing agent, producing the hydrazido complex 2 when reduced with KC 8 , or the dinitride complex 3 when reduced with elemental Mg (this work).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organometallic chemists have studied metal-N 2 systems since the seminal report of A. D. Allen [4] who described the first transition metal-dinitrogen complex. Over the past 50 years numerous advances have emerged from the luminaries of organometallic chemistry including Schrock, [5] Cummins, [6] Peters, [7] Fryzuk, [8] Evans, [9] Gambarotta, [10] Nishibiashi, [11] Holland, [12] Chatt, [13] and Liddle [14] among others. [15] Avenues to metal-mediated N 2 chemistry have typically involved stoichiometric reductants.…”
Section: In Memory Of Nicholas C Paynementioning
confidence: 99%
“…Due to the high Lewis acidity of titanium(IV) centers, the isolation of coordinatively unsaturated titanium(IV) complexes of triamidoamine ligands with TMP geometry is more difficult. No structurally characterized titanium triamidoamine complexes of TMP geometry in the solid state have been reported so far . By using the 3,5‐dimethylphenyl‐substituted triamidoamine ligand [{(3,5‐Me 2 C 6 H 3 )NCH 2 CH 2 } 3 N] 3− , we report herein on thermally stable titanium(IV) cations with TMP geometry around the titanium center.…”
Section: Introductionmentioning
confidence: 99%